Discussion: Foundation design for gravity retaining walls under earthquake - Pender, MJ; Conti, R; Caputo, G; Viggiani, G (Emerald, 2019)
The discussers read the paper by Pender (2018) with great interest. The author addresses the important issue of computing the pseudostatic critical acceleration of gravity/cantilever retaining walls, corresponding to which a plastic mechanism is activated within the soil–structure system and the wall starts to move under the applied earthquake. In fact, the critical acceleration is the key ingredient for the seismic design of these structures, controlling both the maximum internal forces and the final displacement (Conti and Caputo, 2018; Conti et al., 2013).
Keywords: 37 Earth Sciences; 4005 Civil Engineering; 40 Engineering; 3705 Geology